AL-ITTIJĀHĀT AL-JADĪDAH FI TA'LĪM AL-NAHWI FI INDUNISIA (DIRĀSAH TAHLĪLIYAH LI AL-MUALLIFĀT AL-MUKHTAṢARAH LI QIRĀAH AL-KUTUB) - Basith, Abdul (ALSINATUNA, 2022)
This research based on the phenomenon of the publishing various kinds of fast methods to reading the yellow book in Indonesia since the 2000s. This phenomenon is considered as a reaction to the difficulty of learning nahwu and practicing it in reading the yellow book. This study uses a qualitative approach to the type of library research. The data were taken from 7 (seven) books on the fast method to reading the yellow book, which were published from 2001 to d. 2018 namely: al-'Arabiyyah li Gair al-Arab, al-Mu'allim Method in Sharaf and Nahwu, Ibtida'i, Amtsilati, Book of Method 33, al-Miftah li al-'Ulum, and Manhaji. The analytical method used is content analysis. The results of this study indicate that the book method of reading the yellow book (kitab bald) is oriented to 5 (five) competencies, namely: reading skills (loud and silent), understanding Arabic Grammar (theoretical and practical), I'rab, understanding of the Qur'an. , and writing skills (guided, free and dictation). Thus the orientation of nahwu learning has been renewed with the existence of writing skills in al-'Arabiyyah li Gair al-Arab and nahwu learning to understand the Qur'an in Amtsilati and Manhaji.